Attractors of multivalued dynamical processes in topological space with inverse time - Kapustyan, A.V.; Melnic, V.S.; Valero, J. (Нелинейные граничные задачи, 2002)
In this paper we define and study multivalued dynamical processes with inverse time in Hausdorff topological spaces. Existence theorems for attractors of such processes are proved, their topological properties are studied.